NON SURGICAL LATROGENIC PERFORATION REPAIR USING MINERAL TRIOXIDE AGGREGATE AND DIRECT RESTORATION WITH FIBER POST ON CENTRAL MAXILLARY INCISOR - Hendargo Agung Pribadi; Yulita Kristanti (Universitas Gadjah Mada, 2017)
Perforation can be a problem that leading to root canal treatment failure in the long run. Perforation can be caused by iatrogenic factor. The most common iatrogenic perforation was found at maxillary anterior. Non surgery iatrogenic perforation repair can be done using mineral trioxide aggregate and direct restoration. The purpose of this case report was to describe non surgical iatrogenic perforation repair using mineral trioxide aggregate and direct restoration with fiber post. A 27 years old male patient diagnosed for pulpitis came to RSGM Prof. Soedomo. Root canal treatment (pulp extirpation) had performed before he was referred for further treatment. Objective test showed both percussion and palpation were negative. From periapical radiograph could be noticed that there was no file left in the root canal. Root canal treatment was performed using step back technique and lateral condensation. Perforation was sealed by mineral trioxide aggregate. The tooth was restored using direct restoration with fiber post. Latrogenic perforation can be treated non surgically using mineral trioxide aggregate and directly restored using composite resin with fiber post.